Kinematics Model of a Novel （（3-RPR+R）&UPS）+P Hybrid Machine Tool Mechanism - Ying Mei; Wenwen Xu; Denggao Shen (Jixie chuandong)
In order to realize the multi-axis linkage machining of large slender integral structural parts，the new （（3-RPR+R） & UPS） + P hybrid machine tool mechanism with five degrees of freedom is proposed. The inverse kinematics model of the hybrid machine tool mechanism is established by using analytic vector method，and on this basis，the first-order and second-order kinematic influence coefficient matrices are obtained according to the kinematic influence coefficient method，and a more complete inverse kinematics model is established. Finally，the inverse kinematics model of the hybrid machine tool mechanism is solved by Matlab and simulated by Adams，and the results are basically consistent，which verifies the correctness of the inverse kinematics model of the hybrid machine tool mechanism.